Model for Improving The Growth of Real Gross Domestic Product of Pakistan (Business and Economic Analysis Journal, 2022)
The purpose of this paper is to understand the impact of export, investment and foreign economic assistance ( foreign aid) variables on RGDP of Pakistan, in order to identify and implement appropriate strategies that will have a significant impact on overall economic growth. The time series data obtained from secondary sources, have been taken to investigate relationship exists among the variables, during the period of 1990-2020. It included data from State Bank Of Pakistan(SBP), Pakistan Bureau Of Statistics(PBS), Pakistan Economic Survey(PES). First of all “Augmented Dickey and Fuller(1979)[ADF]” test was applied to check the stationary of data, which showed that all variables are stationary at the first difference. EG-ECM methodology was applied to check the short-run and long-run estimation. Based on results of regression analysis, it is concluded that investments (INV) has significant impact on RGDP in both short-run and long-run. Export (X) and foreign economic assistance (FEA) have no impact in short-run, however showed significant impact in long-run. Based on the findings, the study suggests that government should facilitate the exporters to export semi-finished or finished goods, rather than raw material in order to increase their incentive and providing employment opportunities to locals. The State Bank Of Pakistan (SBP) and ministry of finance should focus on promoting INV through savings policies, in order to meet the gap between savings and investments. Pakistan should reduce his rely on foreign funding and needs to improve his domestic savings and investment to gain financial independence. FEA should only be use for productive purposes, infrastructural development and for the betterment of people.